(3LQjeI JdhjK GdHjFI (B:s (3OQGSI ebGQfI (B/s - (3GdedcGhj, EHJSGe SYjO eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2009)
(3jJfGhd cJGH (B((3LQjeI JdhjK GdHjFI(B) (3hGdPj bGe HJCdjag (B((3EHJSGe SYjO GdedcGhj(B) (3aj MhGdj (B(143) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3bGfhf JdhK GdHjFI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdebOeI, GdaUd GdJegjOj (B: (3GdJYGQja hGdebOeGJ GdCSGSjI, GdaUd GdChd (B: (3hVY LQjeI JdhjK GdHjFI aj GdJTQjYGJ, GdaUd GdKGfj (B: (3VhGHW JWHjb LQjeI JdhjK GdHjFI, GdaUd GdKGdK (B: (3GdJcjja GdbGfhfj dLQjeI JdhjK GdHjFI, GdaUd GdQGHY (B: (3GdJUOj dLQjeI JdhjK GdHjFI (B... (3EdN(B.s
(3JUeje hEfJGL (B: (3eQcR OGQ GdKbGaI ddJUeje hGdEfJGL(B.s
(3GdCUd QSGdI eGLSJjQ, LGeYI YeGf GdYQHjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B139-143.s
Keywords: (3GdLQjeI hGdeLQehfs -- (3bhGfjf hJTQjYGJs; (3JdhK GdHjFIs -- (3bhGfjf hJTQjYGJs